Pengaruh Financial Behavior terhadap Kinerja Keuangan UMKM Studi Kasus pada Industri Ritel Parfum di Bali - Nur Samsi; Komang Sri Widiantari (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Retail perfume MSMEs in Bali have experienced rapid growth; however, they continue to face challenges in financial management. The financial behavior of business owners such as overconfidence, anchoring, loss aversion, and risk aversion has the potential to influence the quality of financial decision-making and ultimately affect MSME financial performance. Therefore, this study aims to analyze the effects of these four financial biases on the financial performance of retail perfume MSMEs in Bali. This research employs a quantitative approach involving 100 respondents who are owners or managers of retail perfume MSMEs in Bali. Data were collected through questionnaires that had been tested for validity and reliability. Multiple linear regression analysis was used to examine the effect of each financial behavior variable on financial performance. The results indicate that all four financial behavior variables overconfidence, anchoring, loss aversion, and risk aversion have a negative and significant effect on MSME financial performance. These findings suggest that the higher the level of behavioral financial bias possessed by business actors, the lower the resulting financial performance. Psychological biases in financial decision-making are proven to be factors that weaken the effectiveness of MSME financial management. Therefore, reducing behavioral biases and improving analytical capabilities are necessary for MSME actors to make more rational financial decisions and enhance business financial performance.